BaTiO3 Nanoparticles Embedded Antibacterial Cotton Fabric with UV Protection Characteristics. Issue 1 (31st December 2023) - Kumar, Amit; Sharma, Moolchand; Vaish, Rahul
ABSTRACT: Barium Titanate (BaTiO3 ) nanoparticles were mixed with a stock paste containing an acrylate-based binder to prepare pigment paste. The formulated paste was applied to the cotton fabric by utilizing screen printing followed by drying and curing. The coated fabric was characterized for surface and elemental composition and uniform deposition of BaTiO3 nanoparticles was observed with minimal agglomeration. The resultant fabric showed an effective bacterial reduction greater than 99% against Escherichia coli and Staphylococcus aureus, and after 15 laundering cycles, the modified fabric showed a bacterial reduction of over 98%. The loaded fabric is capable of blocking harmful ultraviolet (UV) radiations. The modification of the cotton surface did not significantly change its intrinsic properties like water vapor permeability, air permeability, fabric stiffness, and other mechanical properties. The developed product has considerable possibilities and provides a good substitute for antibiotic materials for use in medical products and everyday apparel.